Farmers’ perceptions on Drought, Technological preferences in Drought mitigation and their Implications in Mulberry Sericulture in South India - Santhi, Mahima; Rajaram, S (Journal of Extension Education, 2022)
Due to widespread monsoon irregularities, farmers are facing drought situations intermittently. Farmers’ participatory rural appraisal was conducted in selected silkworm growing clusters of South India covering 300 farmers to determine how sericulture farmers perceive and cope with drought, to study the technological preferences and their implications in mulberry, Morus alba leaf production & rearing of silkworm, Bombyx mori. The study revealed that drought is a major constraint for silk cocoon production among 84 per cent of total farmers surveyed. The local drought perceptions described by farmers were acute water shortage, dry and desiccating wind, drying of leaves in the silk worm rearing shed disease outbreak in silkworms, spinning of small size cocoons, higher melting of cocoons and lesser Silk Ratio. While studying the technological preferences, it was observed that farmers gave more importance to technologies which have direct impact on silk cocoon yield.